Is the information fit for use? Exploring teachers perceived information quality indicators for Farsi web-based learning resources - Mohammadi, Faegheh; A., Abrizah; Maryam, Nazari; Mohammadi, Faegheh; Abrizah, A.; Nazari, Maryam (Malaysian Journal of Library and Information Science, 2017)
Mohammadi, F., Abrizah, A., & Nazari, M. (2015). Is the information fit for use? Exploring teachers perceived information quality indicators for Farsi webbased learning resources. Malaysian Journal of Library & Information Science, Vol.20, no. 1: 99-122 This paper explores teachers’ perceived information quality indicators of Farsi Web-based Learning Resources (WBLRs) for instructional use. This research positions information quality as “information fit for use”, which implies that it is relative, as information considered appropriate for one’s use may not have sufficient attributes for another’s use. The research employs a qualitative case study approach completed in two phases. A secondary smart school in Tehran Iran was chosen as the case setting. First, two focus group interviews were conducted with ten teachers, followed by face-to-face interviews with five teachers who were recruited from the focus groups. Next, five students were recruited for face-to-face interviews as an additional data source. Fourteen (14) information quality indicators emerged from the data in conjunction with four categories namely pedagogical usability, content, presentation and accessibility. These information quality indicators provide the web information content designers and producers with in-depth insights on the issues need to be considered when designing and publishing educational web resources, in general, and Farsi resources, in particular. It also can be of value to librarians who are engaged with evaluating and selecting desirable web-based information resources aimed to add such resources into their library holdings.